Probiotic Properties and Potentiality of Lactiplantibacillus plantarum Strains for the Biological Control of Chalkbrood Disease - Massimo Iorizzo; Bruno Testa; Sonia Ganassi; Silvia Jane Lombardi; Mario Ianiro; Francesco Letizia; Mariantonietta Succi; Patrizio Tremonte; Franca Vergalito; Autilia Cozzolino; Elena Sorrentino; Sonia Petrarca; et al. (Journal of Fungi, 2021)
Ascosphaera apis is an entomopathogenic fungus that affects honeybees. In stressful conditions, this fungus (due not only to its presence, but also to the combination of other biotic and abiotic stressors) can cause chalkbrood disease. In recent years, there has been increasing attention paid towards the use of lactic acid bacteria (LAB) in the honeybees’ diets to improve their health, productivity and ability to resist infections by pathogenic microorganisms. The screening of 22 strains of Lactiplantibacillus plantarum, isolated from the gastrointestinal tracts of honeybees and beebread, led to the selection of five strains possessing high antagonistic activity against A. apis. This study focused on the antifungal activity of these five strains against A. apis DSM 3116 and DSM 3117 using different matrices: cell lysate, broth culture, cell-free supernatant and cell pellet. In addition, some functional properties and the antioxidant activity of the five L. plantarum strains were evaluated. All five strains exhibited high antagonistic activity against A. apis, good surface cellular properties (extracellular polysaccharide (EPS) production and biofilm formation) and antioxidant activity. Although preliminary, these results are encouraging, and in future investigations, the effectiveness of these bacteria as probiotics in honeybee nutrition will be tested in vivo in the context of an eco-friendly strategy for the biological control of chalkbrood disease.